Characterization of Brucella abortus O-Polysaccharide and Core Lipopolysaccharide Mutants and Demonstration that a Complete Core Is Required for Rough Vaccines To Be Efficient against Brucella abortus and Brucella ovis in the Mouse Model - Monreal, D. (American Society for Microbiology (ASM), 2003)
Brucella abortus rough lipopolysaccharide (LPS) mutants were obtained by transposon insertion into two wbk genes (wbkA [putative glycosyltransferase; formerly rfbU] and per [perosamine synthetase]), into manB (pmm [phosphomannomutase; formerly rfbK]), and into an unassigned gene. Consistent with gene-predicted roles, electrophoretic analysis, 2-keto-3-manno-d-octulosonate measurements, and immunoblots with monoclonal antibodies to O-polysaccharide, outer and inner core epitopes showed no O-polysaccharide expression and no LPS core defects in the wbk mutants. The rough LPS of manB mutant lacked the outer core epitope and the gene was designated manB(core) to distinguish it from the wbk manB(O-Ag). The fourth gene (provisionally designated wa**) coded for a putative glycosyltransferase involved in inner core synthesis, but the mutant kept the outer core epitope. Differences in phage and polymyxin sensitivity, exposure or expression of outer membrane protein, core and lipid A epitopes, and lipid A acylation demonstrated that small changes in LPS core caused significant differences in B. abortus outer membrane topology. In mice, the mutants showed different degrees of attenuation and induced antibodies to rough LPS and outer membrane proteins. Core-defective mutants and strain RB51 were ineffective vaccines against B. abortus in mice. The mutants per and wbkA induced protection but less than the standard smooth vaccine S19, and controls suggested that anti O-polysaccharide antibodies accounted largely for the difference. Whereas no core-defective mutant was effective against B. ovis, S19, RB51, and the wbkA and per mutants afforded similar levels of protection. These results suggest that rough Brucella vaccines should carry a complete core for maximal effectiveness.